A rare cause of hepatomegaly in the childhood: Lysosomal acid lipase deficiency - Haznedar, Pınar; Kuloğlu, Zarife; Kansu, Aydan; Eminoğlu, F. Tuba (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Haznedar P, Kuloğlu Z, Kansu A, Eminoğlu FT. A rare cause of hepatomegaly in the childhood: Lysosomal acid lipase deficiency. Turk J Gastroenterol 2018; 29: 518-9.